2014
DOI: 10.1172/jci73419
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic nuclear corepressor 1 regulates cholesterol absorption through a TRβ1-governed pathway

Abstract: Transcriptional coregulators are important components of nuclear receptor (NR) signaling machinery and provide additional mechanisms for modulation of NR activity. Expression of a mutated nuclear corepressor 1 (NCoR1) that lacks 2 NR interacting domains (NCoRΔID) in the liver leads to elevated expression of genes regulated by thyroid hormone receptor (TR) and liver X receptor (LXR), both of which control hepatic cholesterol metabolism. Here, we demonstrate that expression of NCoRΔID in mouse liver improves die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 66 publications
2
25
0
Order By: Relevance
“…Further work will be required to determine how hepatic cholesterol is increased in this model, given that we have recently shown that expression of NCoR⌬ID reduces hepatic cholesterol accumulation via a decrease in cholesterol absorption ( Fig. 3D and E) (21).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further work will be required to determine how hepatic cholesterol is increased in this model, given that we have recently shown that expression of NCoR⌬ID reduces hepatic cholesterol accumulation via a decrease in cholesterol absorption ( Fig. 3D and E) (21).…”
Section: Resultsmentioning
confidence: 99%
“…6A). To genetically confirm a TR-specific pathway for the activation of ChREBP and because liver X receptor (LXR) has also been shown to regulate expression of ChREBP and interact with NCoR1, we used a model where the principal hepatic LXR isoform (LXR␣) has been deleted in either the presence or absence of (5,21,33,34). In these animals the hepatic expression of NCoR⌬ID clearly activates the expression of both ChREBP isoforms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcriptional changes in naïve CD4 + T cells caused by the absence of NCOR1 led to the dysregulation of pathways and hallmark gene sets associated with various cellular processes. NCOR1, via binding to LXR, has been described as a key regulator for repressing cholesterol homeostasis-related genes in hepatocytes (46). The observation that cholesterol homeostasis gene sets are enriched in NCOR1-deficient CD4 + T cells suggests that NCOR1 has also a similar repressive function in naïve CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…An important TH target organ is the liver. TH prominently regulate pathways involved in lipid metabolism and cholesterol physiology (Astapova et al., , ), and many clinical parameters of liver function are dependent on systemic TH status (Johansson et al., ). TH receptors also cross talk with liver X receptors to regulate genes involved in lipid metabolism pathways (Hashimoto and Mori, ).…”
Section: Thyroid Hormones and Adult Livermentioning
confidence: 99%